2020
DOI: 10.1007/s00122-020-03621-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parent multi-environment QTL analysis: an illustration with the EU-NAM Flint population

Abstract: Key message Multi-parent populations multi-environment QTL experiments data should be analysed jointly to estimate the QTL effect variation within the population and between environments. Abstract Commonly, QTL detection in multi-parent populations (MPPs) data measured in multiple environments (ME) is done by analyzing genotypic values ‘averaged’ across environments. This method ignores the environment-specific QTL (QTLxE) effects. Running separate single environment an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 37 publications
3
32
1
Order By: Relevance
“…Giraud et al (2014) found that their haplotype model outperformed the founder and SNP models in terms of the number of QTL identified using EU-NAM Flint and Dent maize populations. In contrast, Garin et al (2020) found that in the EU-NAM Flint population, the bi-allelic model detected a larger number of unique QTL, compared to parental or ancestral haplotype models. Bardol et al (2013) found that in two multi-parent dent populations, their bi-allelic model and ancestral haplotype model generally outperformed the parental linkage model, although benefits of these models varied by dataset.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Giraud et al (2014) found that their haplotype model outperformed the founder and SNP models in terms of the number of QTL identified using EU-NAM Flint and Dent maize populations. In contrast, Garin et al (2020) found that in the EU-NAM Flint population, the bi-allelic model detected a larger number of unique QTL, compared to parental or ancestral haplotype models. Bardol et al (2013) found that in two multi-parent dent populations, their bi-allelic model and ancestral haplotype model generally outperformed the parental linkage model, although benefits of these models varied by dataset.…”
Section: Discussionmentioning
confidence: 65%
“…The fact that the QTL F model outperformed the QTL H and GWAS SNP in our population suggests that the MAGIC population contains a relatively more diverse representation of European and North American flint and dent than populations used in previous studies. It is also possible that the structure of multi-parent populations has an effect on the performance of the three models, compared to previous studies which used nested association mapping (Giraud et al 2014;Garin et al 2020) and factorial populations Bardol et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, yet this approach has not been applied to introgress and map these QTLs in the Egyptian rice genetic background. Marker-assisted introgression of QTLs, with major effects for GY under water-deficit stress, are considered a fast-track approach for breeding high-yielding water shortage tolerant rice genotypes [ 20 ]. Because of these major effects, QTLs should be tested across different genetic backgrounds and across environments to check the consistency of their effect.…”
Section: Introductionmentioning
confidence: 99%
“…In humans it is common to study genotype-phenotype associations in population-based samples for genome-wide association studies (GWAS); in model organisms complex breeding designs are often used. Linear mixed models (LMMs) 3–6 are employed for controlling confounding due to genetic relatedness among individuals and are used to identify genetic loci contributing to quantitative traits of interest (QTL) 713 . Multivariate LMMs (MLMMs) further enhance statistical power over univariate LMMs 14 because they can accumulate signals across traits 8, 15 with a common genetic locus.…”
mentioning
confidence: 99%
“…to provide stable, fast convergence 5, 14 . The computational complexity is O ( n 3 m 3 ) for EM and O ( n 3 m 7 ) for NR, AI ( m traits, n individuals). This suggests that using GCTA, WOM-BAT, and ASReml is not practical for GWAS with a large number of SNPs and a moderate number of individuals 14 .…”
mentioning
confidence: 99%